The Labor Market Impact of Immigration in Western Germany in the 1990's - Francesco D'Amuri; Gianmarco I. P. Ottaviano; Giovanni Peri (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
In this article we measure the effects of recent immigration on the Western German labor market looking at both wage and employment effects. Refining administrative data for the period 1987-2001 to account for ethnic German immigrants and immigrants from Eastern Germany, we find that the substantial immigration of the 1990's had very little adverse effects on native wages and on their employment levels. Instead, it had a sizable adverse employment effect as well as a small adverse wage effect on previous waves of immigrants. These asymmetric results are partly driven by a higher degree of substitution between old and new immigrants in the labor market. In a simple calculation we show that the largest aggregate effect of new immigration on natives and old immigrants comes from the increased costs of unemployment benefits to old immigrants. Those costs could be eliminated in a world of wage flexibility and no unemployment insurance in which immigration would not have any negative employment effect but only moderate wage effects.
Keywords: F22; F24; 330; International Migration; Remittances